A Research Agenda on Data Supply Chains (DSC) - Spanaki,K; Adams,R; Mulligan,C; Lupu,E (2016)
Competition among organizations supports initiatives and collaborative use of data whilecreating value based on the strategy and best performance of each data supply chain.Supporting this direction, and building on the theoretical background of the supply chain, wepropose the Data Supply Chain (DSC) as a novel concept to aid investigations for data-drivencollaboration impacting organizational performance. In this study we initially propose adefinition for the DSC paying particular attention to the need for collaboration for the supplychains of data. Furthermore, we develop a conceptual model of DSC collaboration couplingtheoretical background of strategy and operations literature including, the resource-basedview (RBV), supply chain management (SCM) and collaboration (SCC). Finally, we setpropositions and a future research agenda including testing and validating the model fit.